Stability of basement-rooted faults in the Delaware Basin of Texas and New Mexico, USA. (August 2021) - Morris, Alan P.; Hennings, Peter H.; Horne, Elizabeth A.; Smye, Katie M.
Abstract: Since 2009 the Delaware Basin of Texas and New Mexico has experienced increased seismicity related to oilfield operations. Available, near present-day principal stress orientations, relative magnitudes, and vertical stress estimates are integrated to characterize 20 stress domains in the Delaware Basin. Data density, variability, and quality inform classification of most-likely, less likely, and least likely stress tensor fields. A new interpretation of Delaware Basin, 3D basement-rooted faults is analyzed for stability using most-likely stress tensors. Fault stability is expressed in terms of slip tendency ( T s ) and critical pore pressure ( ΔP fc ). Individual faults are compared in terms of their stability and potential seismic capability, and stress scenarios can be compared for their effects on fault stability. Faults range from stable to critical under the conditions investigated, 8% of total mapped fault area may become critically stressed by small pore-pressure increases (1 MPa, 145 psi) above ambient. Comparison of stability measures with focal mechanisms of recent pore-pressure-induced seismicity indicates that T s and ΔP fc have predictive value. This work provides critical information for earthquake hazard and mitigation studies in the Delaware Basin. Highlights: Comprehensive stress model of a highly productive hydrocarbon province. Application of stress model to a detailed basin-scale 3-D fault structure model. Regional fault stability measures compared with recent seismicity. New representations of fault stability and potential for induced seismicity. Comprehensive data repository for public use.